2002
DOI: 10.1021/bi015770h
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 Triglycerides Modify Blood Clearance and Tissue Targeting Pathways of Lipid Emulsions

Abstract: Omega-3-rich (n-3) triglycerides (TG) are increasingly recognized as having modulating roles in many physiological and pathological conditions. We questioned whether the catabolism of lipid emulsions would be changed after enrichment with fish oil (n-3) TG as compared to enrichment with omega-6-rich soy oil (n-6) TG. Phospholipid-stabilized emulsions of n-3 TG and n-6 TG were labeled with [(3)H]cholesteryl oleoyl ether and administered by bolus injection to wild-type (WT) mice, mice lacking the low-density lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 51 publications
4
56
0
Order By: Relevance
“…Using labeled chylomicrons and emulsions, Hultin et al (81) found a large amount of uptake of core lipids into peripheral tissues. A similar observation was recently made by Qi et al (82), who noted that uptake of cholesteryl esters was modified by the lipid composition of emulsions. How does this occur?…”
Section: Lpl In the Heartsupporting
confidence: 84%
“…Using labeled chylomicrons and emulsions, Hultin et al (81) found a large amount of uptake of core lipids into peripheral tissues. A similar observation was recently made by Qi et al (82), who noted that uptake of cholesteryl esters was modified by the lipid composition of emulsions. How does this occur?…”
Section: Lpl In the Heartsupporting
confidence: 84%
“…A large body of studies has been conducted to investigate the roles of specific core lipid FAs in blood clearance and tissue delivery (12)(13)(14)(15)(16). However, the metabolism of intravenous lipid emulsions primarily composed of different AG structures has been poorly defined.…”
Section: Discussionmentioning
confidence: 99%
“…For example, lipid emulsions rich in mediumchain TAG were demonstrated to be more efficiently hydrolyzed by LPL or HL than emulsions with long-chain TAG, resulting in rapid clearance of medium-chain TAG emulsions from blood (12,13). On the other hand, lipid emulsions rich in v-3 FAs from fish oil are less efficiently hydrolyzed by LPL but cleared more efficiently as whole particles compared with v-6 emulsion (14)(15)(16).…”
mentioning
confidence: 99%
“…After 24 hours incubation at 37°C, LDL was re-isolated by sequential gradient ultracentrifugation, and apoB was then labeled with the ALEXA fluorophore according to the manufacturer's method. Isolated LDL was applied to a Sepharose CL-2B gel filtration column (Sigma-Aldrich) (28) to ensure that BODIPY-C12 and ALEXA fluorescence labeling did not alter LDL homogeneity and co-eluted with the LDL fraction (as determined by fluorometry). In separate experiments, fluorescent-labeled LDL cell binding and uptake and LDL-CE SU were compared with those of radiolabeled [ 125 I]LDL in vitro in cultured fibroblasts and showed similar results in both LDL binding and cell association (data not shown).…”
Section: Methodsmentioning
confidence: 99%